The Msh5 complex shows homeostatic localization in response to DNA double-strand breaks in yeast meiosis - Shinohara, Miki; Shinohara, Akira (Frontiers in Cell and Developmental Biology, 2023)
Meiotic crossing over is essential for the segregation of homologous chromosomes. The formation and distribution of meiotic crossovers (COs), which are initiated by the formation of double-strand break (DSB), are tightly regulated to ensure at least one CO per bivalent. One type of CO control, CO homeostasis, maintains a consistent level of COs despite fluctuations in DSB numbers. Here, we analyzed the localization of proteins involved in meiotic recombination in budding yeast xrs2 hypomorphic mutants which show different levels of DSBs. The number of cytological foci with recombinases, Rad51 and Dmc1, which mark single-stranded DNAs at DSB sites is proportional to the DSB numbers. Among the pro-CO factor, ZMM/SIC proteins, the focus number of Zip3, Mer3, or Spo22/Zip4, was linearly proportional to reduced DSBs in the xrs2 mutant. In contrast, foci of Msh5, a component of the MutSγ complex, showed a non-linear response to reduced DSBs. We also confirmed the homeostatic response of COs by genetic analysis of meiotic recombination in the xrs2 mutants and found a chromosome-specific homeostatic response of COs. Our study suggests that the homeostatic response of the Msh5 assembly to reduced DSBs was genetically distinct from that of the Zip3 assembly for CO control.